(untitled) (Journal of Current and Advance Medical Research, 2025)
Mature cystic teratoma is the common ovarian tumor in women of reproductive age. The malignant transformation of mature cystic teratomas is a rare entity. The most common malignant tumor in mature cystic teratomas is squamous cell carcinoma, A 50 years old postmenopasual women, admitted in a private hospital, Sylhet, Bangladesh with the complaints of feeling of lump in the abdomen for the past 3-4 months, associated with abdominal pain for one week and occasional constipation. The patient was diagnosed clinically as a case of ovarian tumor. CT findings were consistent with dermoid cyst. The patient underwent Total Hysterectomy with Bilateral Salpingo-Oophorectomy (TH with BSO). Histopathological examination confirmed the diagnosis of squamous cell carcinoma arising on mature cystic teratoma. Journal of Current and Advance Medical Research, July 2024;11(2):123-125